Ethical sensitivity and related factors of nurses working in the hospital settings - Ertuğ, Nurcan; Aktaş, Demet; Faydali, Saide; Yalçin, Osman (Acta Bioethica, 2014)
The purpose of the study is to determine the level of ethical sensitivity and related factors of nurses working in the hospital settings. This descriptive study was conducted at a public hospital and a university hospital in Ankara, Turkey between April & July 2012. A total of 111 nurses participated in the study. The data were collected using a data collection tool consisting of two parts. The first part consisted of questions that determined the nurses’ personal and socio-demographic characteristics. The second part comprised of “Byrd’s Nurses Ethical Sensitivity Test”. The data were evaluated by using frequency, percentage, t-test and one-way ANOVA. Of the 111 nurses, 39,7% had a work experience of 1–3 years, 51,4% was married and 38,7% did not have ethics education. Education levels of most of the nurses (62,2%) were bachelor’s degree. The mean ethical sensitivity score of nurses was 21,12±2,85. “It was determined that ethical sensitivity of nurses was found to be higher in those that had ethics education, older age group, and had bachelor’s degree than others (p<0,05)”. The mean ethical sensitivity score of nurses was of medium level. It is concluded that ethical sensitivity was influenced by ethics education, age groups, and educational background.